Saving Behavior In Generation Z - Rahayu, Yulianita; Nurfauziah, Farah Latifah (Universitas Muhammadiyah Sorong, 2020)
Penelitian ini memfokuskan pada pengetahuan keuangan dan perilaku menabung pada generasi Z di Kota Bandung. Tujuan dari penelitian ini adalah untuk mengetahui tingkat pengetahuan keuangan generasi Z dan menghubungkan pengetahuan keuangan dengan serangkaian informasi terhadap perilaku menabung generasi Z. Penelitian ini menggunakan kuesioner yang dibagikan kepada responden sebanyak 160 orang dan dianalisis melalui validitas, reliabilitas dan regresi linear sederhana.Â Hasil penelitian in menunjukkan bahwa pengetahuan keuangan memiliki pengaruh tidak signifikan terhadap perilaku menabung, serta memiliki korelasi yang rendah antara pengetahuan keuangan dan perilaku menabung.In this globalization era, increasing financial literacy, saving awareness, and access to formal financial services are needed to be able to provide benefits for improving welfare and economic conditions. The well-literate young generation will have an influence in creating a more stable state economy. This research focuses on financial knowledge and saving behavior in Generation Z in Bandung. The aimed of this study is to determine the level of financial knowledge of generation Z and relate financial knowledge with a series of information on saving behavior of generation Z. This study used a questionnaire distributed to respondents of 160 people and analyzed through, validation, reliability, and simple linear regression. The results of this study indicate that financial knowledge has no significant effect on saving behavior, and has a low correlation between financial knowledge and saving behavior.